BACK TO SCIENTIFIC PUBLICATIONS ACADEMIC G.S. SAPARGALIEV «MODERNIZATION OF THE CONSTITUTION OF THE REPUBLIC OF KAZAKHSTAN» - Karaev, Алипаша Агаханович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
This article considers the legal views of academician G.S. Sapargaliev concerning constitutional reform of 2007 from a retrospective position. Experience shows, that many of the ideas contained in the work, are still relevant today and continues to demand in legal science. The author, gives a detailed commentary of its main provisions, to make suggestions about the need to improve the mechanisms of interaction between the President and the branches of government, based on the study of the Law "On introducing amendments and addenda to the Constitution of the Republic of Kazakhstan", from the position and demands of the time. In its work, the academician Sapargaliyev G.S. pays special attention to the consideration of the President, the issues of expansion of control functions of the Parliament against the executive power, the need for further improvement of the forms of parliamentary control, the electoral law and party system of the Republic of Kazakhstan. Article substantiates a conclusion, that the modernization of the Constitution of the Republic of Kazakhstan is necessary for the formation of a presidential-parliamentary system of government, the creation of the constitutional foundations of deep transformations in all spheres of life of Kazakh society and the state.